Effectiveness of Interventions in Enhancing the Mental Health of Persons with Intellectual Disability: A Systematic Literature Review - Jacob, Udeme Samuel; Gbolade Opesemowo, Oluwaseyi Aina; Pillay, Jace (Journal of Intellectual Disability - Diagnosis and Treatment, 2026)
Introduction: Mental health conditions are significantly more prevalent among individuals with intellectual disability (ID) compared to the general population, yet tailored interventions remain limited. This review synthesises recent evidence on the effectiveness of interventions designed to enhance mental health outcomes in this group, focusing on approaches adapted to their cognitive and social needs. Methods: A systematic literature review was conducted following PRISMA guidelines. PubMed, PsycINFO, Web of Science, Scopus, and the Cochrane Library were searched for studies published between 2020 and 2025. A total of 901 records were screened, with 12 empirical studies meeting the inclusion criteria. Eligible studies evaluated interventions targeting mental health outcomes among individuals with ID using quantitative research designs. Findings: Interventions identified included cognitive-behavioural therapy, mindfulness-based practices, physical and cognitive training, integrative healthcare, peer mentoring, psychoeducation, and technology-assisted approaches. Adapted cognitive-behavioural and mindfulness interventions improved emotional regulation, coping, and quality of life. Physical activity programmes and peer mentoring fostered resilience and social inclusion, while technology-assisted therapies showed feasibility and acceptability. However, outcomes varied according to participant characteristics, delivery methods, and contextual factors. Notably, gaps remain in standardising outcome measures and assessing long-term sustainability. Conclusion: Evidence suggests that multidisciplinary, individualised, and community-based interventions hold promise for enhancing mental health outcomes in people with ID. Collaborative approaches involving healthcare providers, families, and individuals are essential. Future research should prioritise scalable interventions, professional training, and policy integration to ensure equitable, evidence-based support for this underserved population.